2021
DOI: 10.3390/membranes11070470
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced BDNF Actions Following Acute Hypoxia Facilitate HIF-1α-Dependent Upregulation of Cav3-T-Type Ca2+ Channels in Rat Cardiomyocytes

Abstract: Brain-derived neurotrophic factor (BDNF) has recently been recognized as a cardiovascular regulator particularly in the diseased condition, including coronary artery disease, heart failure, cardiomyopathy, and hypertension. Here, we investigate the role of BDNF on the T-type Ca2+ channel, Cav3.1 and Cav3.2, in rat neonatal cardiomyocytes exposed to normoxia (21% O2) and acute hypoxia (1% O2) in vitro for up to 3 h. The exposure of cardiomyocytes to hypoxia (1 h, 3 h) caused a significant upregulation of the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The negative association was explained by the fact that the higher expression of BDNF can cause overall membrane hyperexcitability in brain structures, and the hyperexcitability is toxic to normal plasticity ( 56 ) and further leads to abnormalities in brain function. However, this explanation is not suitable for the negative association between BDNF and attention with a long-term exposure of hypoxia, as it's been reported that elevation in BDNF level often occurs when the exposure time to HA is short ( 37 ). Long-term exposure to hypoxia, as previous studies have observed that BDNF levels were significantly decreased after an exposure of hypoxia of around 2.3 years compared to sea level ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative association was explained by the fact that the higher expression of BDNF can cause overall membrane hyperexcitability in brain structures, and the hyperexcitability is toxic to normal plasticity ( 56 ) and further leads to abnormalities in brain function. However, this explanation is not suitable for the negative association between BDNF and attention with a long-term exposure of hypoxia, as it's been reported that elevation in BDNF level often occurs when the exposure time to HA is short ( 37 ). Long-term exposure to hypoxia, as previous studies have observed that BDNF levels were significantly decreased after an exposure of hypoxia of around 2.3 years compared to sea level ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF, a prominent factor associated with attention function, may also play a role in the inconsistency of attention variation in HA. BDNF level can be reportedly elevated by both acute hypoxia and intermittent hypobaric hypoxia to promote neurogenesis through BDNF-mediated signaling ( 1 , 37 , 38 ), while chronic hypoxia can result in a decrease in BDNF level ( 39 ). An increase in BDNF can improve attention impairment and some studies have found that increased BDNF levels are associated with inattentive problems ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal rat cardiomyocytes were prepared as described previously [ 10 , 11 ]. Neonatal ventricular myocytes were prepared from 2-8-days-old Wistar rats and maintained at 37 °C under 5% CO 2 in Dulbecco’s modified Eagle’s medium (DMEM) that was supplemented with 10% fetal bovine serum for 24 h, followed by an additional 24 h incubation in DMEM with or without protein kinase inhibitor, or a protein kinase activator (see the figure insets).…”
Section: Methodsmentioning
confidence: 99%